Propriedades estruturais, vibracionais e morfológicas de filmes multiferróicos de La2CoMnO6 - Silva, Antonio Vinnie dos Santos (2016)
Perovskites with double formula in A2BB'06 form (A = La, Sr, Ca, B / B '= Co / Mn or Fe / Mo) are multiferroic materials of great interest in science because of their remarkable properties that allow applications and capacitors in memories, for example. In addition, structural changes are observed between the polycrystalline form and thin film. These properties may change according to the route used for synthesizing the material. In our work we study La2CoMnO6 films synthesized by a modified Pechini method (MPM), with three depositions and treated at different temperatures: 700, 800 and 900 ° C. The films were characterized by X-ray diffraction, scanning electron microscopy (SEM), atomic force microscopy and Raman spectroscopy at room temperature and also varying the temperature. The SEM and AFM were very efficient in determining the diameter medium of film and EDS allowed to get qualitative description of the film composition. The X-ray diffraction confirmed the structural phase of the film. Raman spectroscopy at various points possible to identify the regions were LCMO were grown. The study of the most intense phonon change with temperature showed different transition temperatures for the ferromagnetic-paramagnetic phase, thus allowing us to confirm that the calcination temperature of the films determined the high structural disorder LCMO for films treated at 700 to 900 °C. We discuss our results compound with other studies in literature, which show the magnetic measurements as a determining factor to prove the spin-phonon coupling temperature.